Effect on ruminal lactic acid utilization and lactic acid-utilizing bacteria - G.W. Miller; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1986)
The effect of diet on in vitro lactic acid utilization rate and counts of lactic add-utilizing bacteria was determined in ruminally cannulated steers. The steers were adapted to an alfalfa diet and gradually switched to an all-grain diet. The in vitro lactic acid fermentation rate increased with increased grain intake. Concurrently, the proportion of lactic acid-utilizing bacteria also increased. The increased population of lactic acid-utilizing bacteria is responsible for preventing lactic acid accumulation in the rumen of cattle adapted to consume a high-grain diet.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Ruminal lactic acid; Ruminal lactic acid bacteria; Feed intake